Transparansi Informasi Publik Merupakan Kunci Akuntabilitas dan Pencegahan Korupsi - Putu Eka Pitriyantini; Ida Ayu Windhari Kusuma Pratiwi; Ida Bagus Wirya Dharma (Kertha Wicaksana, 2025)
According to data from the Corruption Eradication Commission (KPK), Indonesia is currently facing a corruption crisis. Therefore, this study aims to offer a trilogy concept in combating corruption. It explores how transparency, accountability, and ethics are interrelated within the context of anti-corruption efforts. This research employs a normative method, specifically prescriptive-analytical, using a conceptual approach, legislative approach, and case study approach to assess the effectiveness of transparency, accountability, and ethics in eradicating corruption. The findings reveal that the implementation of transparency, accountability, and ethics as a trilogy in combating corruption in Indonesia remains ineffective. The study finds that the trilogy concept can become part of law enforcement if supported by the President as both the Head of State and Head of Government. Limitations: This research is limited to the discussion of transparency, accountability, and ethics in anti-corruption efforts. The author hopes that this study can raise awareness among the public, anti-corruption communities, and the younger generation about the dangers of corruption to Indonesia’s future. Contribution: Finally, this research is expected to contribute to the academic field by providing new insights in the study of corruption, law, politics, and public administration.